PERANCANGAN WEBSITE PEMESANAN PRODUK PADA TOKO BY.BINGKISS GUNA OPTIMALISASI PEMESANAN - Dara Kharisma Limparan; Teny Handhayani; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
This research Aimed at improving the customer experience and order management process, this study concentrates on the creation and deployment of the By. Bingkiss online ordering website. The study looks at the specifications for a user-friendly platform that can accommodate registered and unregistered users, so providing simple access to order placement tools, galleries, and product catalogs. Establishing an effective online ordering system that satisfies By. Bingkiss's business demands and offers a flawless user experience is the main goal of this research. The study approach used consists in qualitative interviews with the store owner to ascertain business needs, then in the development of use case diagrams, activity diagrams, and database design (ERD). With MySQL for database administration, PHP is used for the backend and HTML, CSS for the frontend, is constructed. To guarantee the website operates as it should, testing stages including User Acceptance Testing (UAT) were carried out. The results show that by means of a disciplined and easy-to-use user interface, order administration is facilitated, and real-time access to product information helps the By. Bingkiss website effectively fulfill its goals. Establishing regular maintenance rules helps to guarantee that the website stays user-friendly and functional. This study comes to the conclusion that the By.bingkiss website is an essential instrument for improving operational efficiency and customer satisfaction, thereby helping the company to develop.